Study of photovoltaic system performance across different geographical region of Nepal - Karna, Sanjay; Kumar Jha, Ajay; Yadav, Kishori (BIBECHANA, 2025)
The objective of this work is to study the photovoltaic system performance across different geographical region of Nepal and its economic benefits. Nepal's solar irradiation varies significantly by season, from 4.5 kWh/m² in December to 7.2 kWh/m² in May. Notably, May has the highest irradiance levels, whereas December has the lowest. The Himalayan region, including Mustang, Kehami, and Jomsom, has greater irradiance levels ranging from 6 to 6.5 kWh/m²/day. The eastern half of Nepal has lower irradiance values, below 4.4 kWh/m²/day. The palce of high irradiance, has current output ranges from 19 A to 27.5 A, with peak PV power of 375 W when simulated with secondary data. The simulation observation shows temperature fluctuations has influence power output, with higher power at lower temperatures. Also, the power generation by PV rises with decreasing temperature and shifts to optimization voltage. The relationship between global horizontal irradiance and photocurrent is linear and increase from 9 to 19 A. At considered temperatures range the optimum creased photocurrent observed at 45°C. The economic analsyis was done considering 365 W solar PV system in Nepal’s Himalayan region and Eastern Half. The parameters use for economic analysis are Payback Period, Return on Investment (ROI), and Net Present Value (NPV). The analysis show that at higher solar irradiance in the Himalayan region leads to a shorter payback (15.7 years), higher ROI (59.4%), and a less negative NPV in comparative to the Eastern Half of Nepal. These findings highlight the importance of knowing solar irradiance and temperature dynamics for optimizing PV system performance throughout Nepal's different geographical regions.